The VELVET A orthologue VEL1 of Trichoderma reesei regulates fungal development and is essential for cellulase gene expression. - Razieh Karimi Aghcheh; Zoltán Németh; Lea Atanasova; Erzsébet Fekete; Melinda Paholcsek; Erzsébet Sándor; Benigno Aquino; Irina S Druzhinina; Levente Karaffa; Christian P Kubicek (PLoS ONE)
Trichoderma reesei is the industrial producer of cellulases and hemicellulases for biorefinery processes. Their expression is obligatorily dependent on the function of the protein methyltransferase LAE1. The Aspergillus nidulans orthologue of LAE1--LaeA--is part of the VELVET protein complex consisting of LaeA, VeA and VelB that regulates secondary metabolism and sexual as well as asexual reproduction. Here we have therefore investigated the function of VEL1, the T. reesei orthologue of A. nidulans VeA. Deletion of the T. reesei vel1 locus causes a complete and light-independent loss of conidiation, and impairs formation of perithecia. Deletion of vel1 also alters hyphal morphology towards hyperbranching and formation of thicker filaments, and with consequently reduced growth rates. Growth on lactose as a sole carbon source, however, is even more strongly reduced and growth on cellulose as a sole carbon source eliminated. Consistent with these findings, deletion of vel1 completely impaired the expression of cellulases, xylanases and the cellulase regulator XYR1 on lactose as a cellulase inducing carbon source, but also in resting mycelia with sophorose as inducer. Our data show that in T. reesei VEL1 controls sexual and asexual development, and this effect is independent of light. VEL1 is also essential for cellulase gene expression, which is consistent with the assumption that their regulation by LAE1 occurs by the VELVET complex.